THE EFFECTS OF EXTRACURRICULAR AND EXTRASCHOOL ACTIVITIES ON SCHOOL PERFORMANCE - Andrea BARABÁS (National Centre for Policy and Evaluation in Education, 2020)
The socio-economical background of the family influences the school efficiency, but beside this, many other factors have outstanding effect on pupils' results. Most of these factors can be found outside of the educational institutions. The studies which focus on the performance of schooling highlight the idea that extracurricular activities have enormous benefits on the school performance as well as on the overcoming of school failure and abandonment. Our research is focusing on the extracurricular and extraschool activities as well as their effect on the development of competencies. We would like to find out how the extracurricular/ extraschool activities influence the results of competence measurements. We created our background questionnaires, that analyse the effects of influencing factors, since there aren't such questionnaires in the national assesments in Romania. Our study is based on the analysis of the KOV-ET-OM-2017 database (N = 1054), which contains the results of the competency assesment of the 4th grade students belonging of the Hungarian minority from Covasna county and information related to contextual factors from the background questionnaires. The outcome of the research highlights the fact that the extracurricular activities have beneficial effect on the development of the school competences. Among the activities organized by the schools, the camps and the activities supporting the prodigies seem to be the most effective.